ACROSS THE BORDERS OF MADNESS: THE „WASTE LAND‟ OF EDWARD BOND IN GREAT PEACE - Nicolas Roman, Susana (European Scientific Journal, ESJ, 2014)
Edward Bond, l‘enfant terrible of British contemporary theatre,depicts violence and the injustices of our world in all his plays since thesixties. The playwright is determinant in his criticism to the present dramafar from reality and the needs of questions for society. In Great Peace, thethird play of The War Plays trilogy, Bond presents a ‗waste land‘ withapocalyptical shades after a nuclear bombing. Humanity has disappeared anda Woman, with no name, begins her journey to self-knowledge with animagined bundle. Across the borders of madness, she is forced to survive inthis desert to understand the killing of her baby. This ‗mother courage‘ figurewill provide the audience the possibility to reflect upon maternity not as ablood tie but as a connection to justice on the community‘s benefit. Bondproposes the deconstruction of the traditional mother and a redefinition ofthe term in which solidarity and social awareness would replace self-interest.